2006
DOI: 10.1089/jir.2006.26.887
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in Cytokine Secretion on Immune Stimulation with LPS and LTA

Abstract: Immune defense capacity differs between men and women. Whereas men are more prone to infection and sepsis, women more commonly develop autoimmune diseases. We investigated the difference in cytokine secretion between males and females in response to different immune stimuli. Whole blood from 154 healthy volunteers (age 24 +/- 5.2; 82 females, 72 males) was collected within 2 h on 2 consecutive days. Blood from males produced significantly more tumor necrosis factor-alpha (TNF-alpha), interleukin-1beta (IL-1bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
54
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 21 publications
16
54
0
Order By: Relevance
“…This assumption is in line with observations that healthy males produce higher serum levels of pro-inflammatory cytokines, e.g. tumor necrosis factor-alpha (TNF-α ), interleukin-1beta (IL-1 β ), IL-6, and IL-8, to different stimuli (Aulock et al ., 2006). TNF-α levels, in particular, have been shown to inversely correlate with T-cell telomere length (Panossian et al ., 2003).…”
Section: Resultssupporting
confidence: 88%
“…This assumption is in line with observations that healthy males produce higher serum levels of pro-inflammatory cytokines, e.g. tumor necrosis factor-alpha (TNF-α ), interleukin-1beta (IL-1 β ), IL-6, and IL-8, to different stimuli (Aulock et al ., 2006). TNF-α levels, in particular, have been shown to inversely correlate with T-cell telomere length (Panossian et al ., 2003).…”
Section: Resultssupporting
confidence: 88%
“…The effect is dose dependent and associated with increased expression of markers of inflammation [10][11][12]. Similar effects have also been seen in humans, where LPS induces a hypotensive response, associated with an increase in circulating cytokines [13], although females are more resistant, with a lesser increase in temperature, fall in blood pressure, and in vitro release of cytokines [14][15][16]. Few studies have investigated differences in the peripheral blood mononuclear cells responses in pregnant and NP individuals and found that the cytokine (interleukin (IL)-6, IL-10, and IL-17) response was increased in the cells from pregnant women exposed to a variety of agents (umbilical cord blood (UCB) of the mother's own child, third-party UCB, phytohemagglutinin, and anti-CD3 antibody) [17].…”
Section: Introductionmentioning
confidence: 61%
“…Female myelin-specific T cells produce more IFNγ and less Th2 cytokines than male T cells and are more encephalitogenic upon adoptive transfer (9)(10)(11). However, despite numerous attempts to explore this issue in humans (12)(13)(14)(15)(16), conclusive evidence in support of a Th1 bias in women is lacking.…”
mentioning
confidence: 99%